Recent advances in biosensors for in vitro detection and in vivo imaging of DNA methylation - Zhang, Qian; Wu, Yanxia; Xu, Qinfeng; Ma, Fei; Zhang, Chun-yang (Biosensors & bioelectronics, 2021)
DNA methylation is the predominant epigenetic modification that participates in many fundamental cellular processes through posttranscriptional regulation of gene expression. Aberrant DNA methylation is closely associated with a variety of human diseases including cancers. Therefore, accurate and sensitive detection of DNA methylation may greatly facilitate the epigenetic biological researches and disease diagnosis. In recent years, a series of novel biosensors have been developed for highly sensitive detection of DNA methylation, but an overview of recent advances in biosensors for in vitro detection and especially live-cell imaging of DNA methylation is absent. In this review, we summarize the emerging biosensors for in vitro and in vivo DNA methylation assays in the past five years (2015–2020). Based on the signal types, the biosensors for in vitro DNA methylation assay are classified into five categories including fluorescent, electrochemical, colorimetric, surface enhanced Raman spectroscopy, mass spectrometry, and surface plasmon resonance biosensors, while the biosensors for in vivo DNA methylation assay mainly rely on fluorescent imaging. We review the strategies, features and applications of these biosensors, and provide a new insight into the challenges and future directions in this area. 1.We reviewed the recent advances in biosensors for in vitro detection and in vivo imaging of DNA methylation.2.Biosensors for in vitro DNA methylation assay are classified into five categories.3.Biosensors for in vivo DNA methylation assay mainly rely on fluorescent imaging.4.The strategies, features and applications of these biosensors are highlighted.5.The challenges and future directions in this area are discussed.